COMPARATIVE ANALYSIS OF MECHANICAL CHARACTERISTICS OF THE STEELS, APPLIED FOR PRODUCTION OF CHIPPING KNIVES, RECEIVED BY METHODS OF THERMAL AND THERMOMECHANICAL PROCESSINGS - A. V. Alifanov; A. M. Milyukova; V. V. Tsuran (Литьë и металлургия)
Results of researches of chemical composition of chipping knives of foreign and domestic producers are given in the article. Results of mechanical tests of samples with determination of temporary resistance, percentage elongation, ultimate strength at cross bending, bend from the various tool steels, subjected to heat treatment (tempering) and thermomechanical processing with low tempering, are given. Recommendations on use of TO and TMO for investigated steels are given.